Therapeutic Implications of a Polymethoxylated Flavone, Tangeretin, in the Management of Cancer via Modulation of Different Molecular Pathways - El-Shaimaa A. Arafa; Noura T. Shurrab; Manal A. Buabeid (Advances in Pharmacological and Pharmaceutical Sciences)
Chemotherapeutics can induce oxidative stress, inflammation, apoptosis, mitochondrial dysfunction, and abnormalities in neurotransmitter metabolism leading to toxicity. Because there have been no therapeutic strategies developed to target inflammation and oxidative stress, there is a continuing need for new and improved therapy. As a result, there has been increasing interest in complementary and alternative medicine with anticancer potential. Studies have shown that the antioxidant activities and anti-inflammatory effects of citrus fruits are promising natural phytochemicals in the development of new anticancer agents. Tangeretin is a naturally polymethoxylated flavone compound extracted from the citrus peel that has shown significant intestinal absorption and adequate bioavailability, with the added benefit of promoting longevity. In addition, tangeretin is known to exhibit considerable selective toxicity to many types of cancer cell proliferation such as ovarian, brain, blood, and skin cancer. Evidence indicates that tangeretin acts through several mechanisms including growth inhibition, induction of apoptosis, autophagy, antiangiogenesis, and estrogenic-like effects. Furthermore, tangeretin works through mitigating levels of inflammatory mediators in the immune system. Using tangeretin in combination with clinically applied anticancer drugs could be a good strategy for increasing the efficiency of these agents and protecting noncancerous cells from damage caused by chemotherapy. The purpose of this review is to highlight the protective effects of a novel natural product, tangeretin against chemotherapeutic-induced toxicity. The development of chemoprevention strategies can lead to significant health care improvement in cancer survivors. Thus, study outcomes may attract more investigators to conduct tangeretin-related research and find out potentially significant impacts on health care of cancer patients and decreased health problems associated with chemotherapeutics-induced toxicity.